Development and evaluation of modified atmosphere packed passion fruit(Passiflora edulis) - Madhana Supriya R (Department of Post harvest technology and agricultural processingKelappaji College of Agricultural Engineering and Technology, 2012)
Passion fruit is a tropical fruit which is extensively used in juice processing. The fruit is highly perishable and losses its quality immediately after the second day of harvest. The postharvest loss in quality and commercial value is due to the intense respiratory activity and significant moisture loss. Hence a study was undertaken to develop a wax applicator to extend the shelf life of passion fruit by adopting the postharvest technologies. A simple and efficient wax applicator with a capacity of 250 kg.hr-1 was developed based on the physical properties of the fruits. Various samples of the passion fruits were treated with bee wax and commercial wax packed in LDPE bags of 200 and 400 gauge. The effect on the shelf life extension of fruits was investigated individually and in combination of wax and LDPE bags. In the case of LDPE bags, different levels of perforations such as 0%, 0.5%, 1% and 2% were used. The samples were kept in ambient condition viz., 32 - 35°C and 70 - 80% RH and at cold conditions as 7ºC and 90% RH. The physicochemical characteristics of samples were tested periodically at an interval of 5 and 7 days, under ambient and cold storage conditions, respectively. The results obtained were subjected to statistical analysis. From the results it was revealed that the samples kept in non-perforated polythene covers were found to be better than those kept in perforated bags and in normal atmosphere. A maximum shelf life of 40 days was obtained for passion fruits at 7oC coated with commercial wax emulsion. Thus, commercial wax coating in combination with LDPE bags acted as a barrier against moisture loss and respiration rate of fruits. However, the fruits kept as control had lost consumer acceptability after the tenth day of study at cold condition and within two days at ambient storage conditions.